Effect of treated palm fibers on the mechanical properties of compressed earth bricks stabilized by alkali‐activated binder‐based natural pozzolan - Rolande Aurelie Tchouateu Kamwa; Joseph Bikoun Mousi; Sylvain Tome; Juvenal Giogetti Deutou Nemaleu; Martine Gérard; Marie‐Annie Etoh; Jacques Etame (International Journal of Ceramic Engineering & Science)
Abstract The aim of this work is to study the influence of the palm fibers treated with soda hydroxide solution on the properties of the compressed earth bricks stabilized (CEBs) with alkali‐activated binder. The improvement in their mechanical parameters is attributable with 15 wt.% of alkali‐activated binder‐based natural pozzolan. To achieve this objective, mortars composed of treated fibers at different levels (0.1, 0.2, 0.3, 0.4, and 0.5 wt.%) of lengths of 4 and 16 cm have been developed. These different mortars with and without fibers were subjected to mechanical (dry and wet compressive test, flexural test), physical (water absorption), mineralogical (XRD, FTIR), and microstructural (SEM/EDS) characterizations after 7 and 90 days. The results revealed that in general the incorporation of fibers improves the mechanical and physical properties of CEBs stabilized with 15 wt.% of alkali‐activated binder. Furthermore, the X‐ray diffraction analysis indicated that certain mineralogical phases of the raw materials dissolve during alkaline activation. The Fourier transform infrared spectra revealed the effectiveness of the fibers in sorption water molecules. Moreover, optical examination reveals that the binder utilized completely wraps the fibers. This demonstrates that the treated fibers function flawlessly as a filler in the matrix. At 90 days with the addition of 0.4 wt.% fibers, the maximum dry compressive strength and flexural strength values were 8.08±0.40 and 5.8±0.19 MPa, respectively. The stabilized earth bricks reinforced with 0.4 wt.% of palm fibers exhibited the mechanical properties values fitting the requirements of the materials candidate for the building construction applications especially as masonry bricks.